Development and investigation of thermal insulation from hemp-polylactide fibres - Rūta Stapulionienė (Engineering Structures and Technologies, 2016)
In the last two decades intensive grow of industry of building materials from renewable resources is observed. Such situation is related to some aspects: global warming, environmental pollution, impact on human health, environmental impact of materials at their end-of-life.